2011
DOI: 10.33762/bsurg.2011.55380
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Diode Laser Transcanalicular Dacryocystorhinostomy for the Treatment of Acquired Nasolacrimal Duct Obstruction

Abstract: This study designed to determine the surgical outcome of transcanalicular dacryocystorhinostomy for the treatment of blocked lacrimal pathway. This is a prospective study of 36 patients admitted in Basrah General Hospital from March 2008 to May 2010. The age of the patients was in range from 6 to 60yrs. Forty five (31.25%) were males and 99(68.75%) were females. All of these cases were unilateral. Thirty three (93.05%) of the total patients were operated general local anesthesia and the rest 3 (6.94%) were und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In literature, there are few studies about DCR surgery with and without silicon tubes. While some studies have reported no statistically significant advantage of using DCR with silicon stents over the DCR without stents [ 15 17 ], in the other studies, intubation is recommended in DCR surgery [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, there are few studies about DCR surgery with and without silicon tubes. While some studies have reported no statistically significant advantage of using DCR with silicon stents over the DCR without stents [ 15 17 ], in the other studies, intubation is recommended in DCR surgery [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested the use of silicon tube intubation in NLDO surgery [ 9 , 10 ], while some prefer using silicon tubes only for definitive indications (canalicular damage, lacrimal sac inflammation, secondary surgery, small and contracted sacs, etc.) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%